Utmark i endring - Flemsæter, Frode; Egil Flø, Bjørn (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2021)
In Norway, the outfields [utmark] are understood as mainly un-cultivated countryside areas such as forest and upland and make up over 70 per cent of the country's land area. The outfields are the grounds for land uses such as grazing, forestry, hunting, fishing, recreation, wind- and hydropower production and mining.Major changes are taking place in the Norwegian outfields. Cabin construction, predators, grazing, and an increasing level of conflict between traditional and new users of these areas are causing heated debate about the use of these lands and their resources. In Utmark i endring [Outfields in Transformation], some of the country's leading social scientists in the field provide an overview of the significant changes and insight into how to further the ongoing debate about the future of these outlying areas. The use of the outfields has always been important to Norwegians. It is where weekend homes, wind power, mining and outdoor recreation are creating a certain quality of life - and workplaces. Yet these uses are also challenging our values regarding the natural environment, cultural values and traditional uses of these areas such as sheep and reindeer grazing.Changes in how these areas are valuated and used can lead to several conflicts of interest: Can traditional grazing survive the encroachment by other users and predators?How much expansion of second-home developments can the land tolerate?What should the limit be on adaptation for recreational activities?What aspects of the history of this territory do we value?The contributors to this book come from such various disciplines as geography, sociology, law, economics and philosophy - and therefore have different perspectives on the changes that are occurring. Collectively, the chapters in Utmark i endring make a significant contribution to existing research and can serve as a basis for further discussion of the challenges that businesses, individual users, and custodians of these lands face. Utmark i endring is thought-provoking reading for anyone with an interest in Norwegian land use and management, including students, researchers, business leaders and land managers. With its interesting and socially relevant content, this book is also highly relevant for the average socially engaged citizen. Utmark i endring has been edited by Frode Flemsæter, senior researcher at Ruralis and associate professor at the Norwegian University of Science and Technology (NTNU), and Bjørn Egil Flø, senior researcher at the Norwegian Institute of Bioeconomy Research (NIBIO).; Det er i ferd med å skje store endringar i den norske utmarka. Hyttebygging, rovdyr, beiting og aukande konfliktnivå mellom tradisjonelle og nye brukarar fører til heftige debattar om bruken av utmarka og utmarksressursane. I boka Utmark i endring gjev nokre av landets fremste samfunnsforskarar innanfor feltet utmark ei innføring i viktige endringar, og innspel til korleis ein kan bringe debattane rundt framtida til utmarka vidare.Bruk av utmark har alltid vore viktig for oss nordmenn. Her kan fritidsbustadar, vindkraftutbygging, gruvedrift og friluftsliv skape livskvalitet og arbeidsplassar. Samstundes utfordrar bruken både naturverdiar, kulturverdiar og tradisjonell utmarksbruk som sau- og reinbeite.Arealpresset i utmarka er veksande og kan føre til fleire interessekonfliktar: Kan beitenæringane overleve areal- og rovdyrpress?Kor mange fleire fritidsbustader toler utmarka?Kvar går grensa for tilrettelegging i friluftslivet?Kva for del av utmarkshistoria er det vi verdset?Bidragsytarane i boka kjem frå ulike fagfelt som geografi, sosiologi, jus, økonomi og filosofi - og gjev med dette ulike perspektiv på endringane i utmarka. Samla gir Utmark i endring eit vesentleg bidrag til utmarskforskinga, og kan fungere som eit diskusjonsgrunnlag for dei utfordringane som næringar, brukarar og forvaltarar av utmarka står overfor.Utmark i endring er tankevekkande lesing for alle med interesse for bruk og forvalting av utmarka. Dette kan vere studentar, forskarar, næringsaktørar eller forvaltarar av utmarka. Med eit interessant og samfunnsaktuelt innhald er boka òg høgaktuell for den jamne samfunnsengasjerte borgar. Utmark i endring er redigert av Frode Flemsæter, seniorforskar ved Ruralis og fyrsteamanuensis ved NTNU, og Bjørn Egil Flø, seniorforskar ved NIBIO.